Anti Fungi Potential of Psidium cattleianum afzel ex Sabin extraction as an inhibitor of fungi Fusarium solani - Lina Febriantini; Khotibul Umam; Putu Agus Hendra Wibawa; Wawan Sujarwo (Jurnal Biologi Tropis, 2022)
The use of fungicides plays an important role in controlling plant diseases caused by Fusarium. However, the development of environment friendly fungicides is considered more effective, which used the plant secondary metabolites. This study aims to find the latest alternative fungicides using Psidium Cattleianum Afzel plant extract, ex Sabine from the collection of the "Eka Karya" LIPI-Bali Botanical Garden, which can inhibit the growth of F. solani and to find the minimum dose of the plant extract in inhibiting growth of F. solani. The method used was early screening of plant and fungi, medium preparation for fusarium and minimum dose analyze. This study found that based on 19 plants tested, Psidium cattleianum proved effective in inhibiting the F. solani. ÃÂ Further testing of psidium plants was carried out by looking at the minimum dose of inhibition against fusarium. The inhibition zone contained in the 1% treatment was greater than the concentrations of 0.75%, 0.50% and 0.25%. The research was continued at a concentration reduction of 0.20-0.005% with the results showing that a concentration of 0.20% to a concentration of 0.05% resulted in a moderate inhibition zone of 8 mm to 9.2 mm. Therefore, it can be concluded that the concentration of 1% is the concentration with the minimum dose of Psidium cattleianum in inhibiting the growth of the fungus Fusarium solani.